Neutrophil-derived ratios as predictors of short-term mortality in HBV-associated decompensated cirrhosis - Yang Xiang; WeiLin Mao (BMC Gastroenterology)
Abstract Background Hepatitis B virus-associated decompensated cirrhosis (HBV-DC) is recognized as a critical illness with an increased risk of short-term mortality. Neutrophil-derived ratios, including neutrophil-to-lymphocyte ratio (NLR), neutrophil-to-albumin ratio, neutrophil-to-high-density lipoprotein-cholesterol ratio, neutrophil-to-hemoglobin ratio, and neutrophil-to-platelet ratio, have emerged as potential prognostic markers in various liver diseases. The present study aimed to determine the effectiveness of these neutrophil-derived ratios for prediction of mortality in patients with HBV-DC. Methods We conducted a retrospective analysis of HBV-DC patients at our hospital between April 2022 and April 2024. The study endpoint was the 30-day mortality rate. These neutrophil-derived ratios were calculated from data obtained during routine laboratory tests on admission. Disease severity was assessed using the Model for End-Stage Liver Disease (MELD) score. Multivariate regression analyses and receiver operating characteristic (ROC) curve analyses were conducted. Results The study investigated 160 HBV-DC patients, of whom 23 (14.4%) experienced mortality within 30 days. Non-survivors exhibited markedly higher values for neutrophil-derived ratios than survivors. All neutrophil-derived ratios were associated with mortality in univariate analyses, but only NLR and MELD score remained as independent predictors of mortality in multivariate analyses. In the ROC analyses, NLR showed a similar prognostic value to MELD score. Moreover, both NLR and MELD score had high specificity for prediction of mortality in HBV-DC patients. Conclusions Among neutrophil-derived ratios, NLR stands out as a simple and reliable predictor of mortality in HBV-DC patients.